Developing polycistronic expression tool in Yarrowia lipolytica - Donghan Li; Jianhui Liu; Lingxuan Sun; Jin Zhang; Jin Hou (Synthetic and Systems Biotechnology)
Unconventional oleaginous yeast Yarrowia lipolytica has gained widespread applications as a microbial cell factory for synthesizing various chemicals and natural products. The construction of efficient cell factories requires intricate metabolic engineering. However, multi-gene expression in Y. lipolytica is labor-intensive. To facilitate multi-gene expression, we developed the polycistronic expression tool using 2A peptides. We first compared different 2A peptides in Y. lipolytica and identified two 2A peptides with high cleavage efficiency: P2A and ERBV-1. The effect of 2A peptides on the expression level of upstream and downstream genes was then determined. Ultimately, we applied the identified 2A peptides to express four genes in canthaxanthin biosynthetic pathway within one expression cassette for canthaxanthin production. This study enriches the multi-gene expression tools of Y. lipolytica, which will facilitate the cell factory construction of Y. lipolytica.